THE EVALUATION OF REGIONAL INCOME (PAD) IN CENTRAL SULAWESI PROVINCE IN 2014-2018 - Syamsul Syamsul (Berkala Akuntansi dan Keuangan Indonesia, 2020)
This study aims to evaluate the regional income (PAD) of districts/cities in Central Sulawesi Province in 2014-2018. Based on the descriptive analysis, it was found that of the four sources (components) of PAD, which had an average growth rate of more than 50 percent and a degree of contribution of more than 50 percent, only other legitimate local revenue. Then, the overall PAD growth rate is still very low (less than 30 percent) and is included in the unsuccessful qualification. Meanwhile, the level of contribution of PAD to regional income is still very small (less than 10 percent) and is classified as very poor qualification.